EFFORTS TO IMPROVE SPEAKING ABILITY BY PICTURE SERIES MEDIA OF THE STUDENTS IN B1 GROUP AT BUSTANUL ATHFAL AISYIYAH KENITEN PONOROGO IN ACADEMIC YEAR 2017-2018 - Anifatur Rowiyah; Muhibuddin Fadhli; Ida Yeni Rahmawati (Universitas Muhammadiyah Ponorogo, 2018)
This research aims to: (1) describe and explain the process of speaking ability by picture series media of the students in B1 group at Bustanul Athfal Aisyiyah Keniten Ponorogo in academic year 2017-2018, (2) describe and explain the result of speaking ability by picture series media of the students in B1 group at Bustanul Athfal Aisyiyah Keniten Ponorogo in academic year 2017-2018. The picture series media chosen because it can to train of language skill and expression skill the child (speaking and telling story). The type of this research was classroom action research with Kemmis and Mc Taggart model. The subject of this research was the students of B1 group at Bustanul Athfal Aisyiyah Keniten Ponorogo consisting of 20 students. The data technique were collected by using observation, documentation and interview. Data analysis of this research used the qualitative data and quantitative data. The success indicator in this action research it said success when percentage of speaking ability of the students were 80%. Based on the result of the research show the speaking ability by the picture series able to improve the speaking ability of the students in B1 group at Bustanul Athfal Aisyiyah Keniten Ponorogo in academic year 2017-2018. It showed by the mean percentage of speaking ability by the picture series in pra cycle that have a good criteria that is 15%. In the first cycles percentage of speaking ability by the picture series that have a good criteria that is 30%. In the second cycle percentage of speaking ability by the picture series that have a good criteria increase to 85%. It shows the classroom action research it says success, because the percentage of speaking ability by the picture series of the students get success indicator that is 80%.